Four new species of Astenus (Eurysunius) Dejean, 1833 from Western Anatolia, Turkey (Coleoptera: Staphylinidae, Paederinae) - Anlaş Si̇nan (Zootaxa, 2015)
Four new species of Astenus (Eurysunius) Dejean (Staphylinidae: Paederinae) are described from Western Anatolia, Turkey, and illustrated: Astenus gusarovi sp. n. (Çökelez Mountain, Denizli province), A. orgeli sp. n. (İmambaba Tepesi, Aydın province and Bozdağlar, İzmir province), A. kumlutasi sp. n. (Akdağlar, Kütahya province and Murat Mountain, Uşak province) and A. honazicus sp. n. (Honaz Mountain, Denizli province). Additional records and updated distributions are provided for A. occiduus Assing, A. sultanicus Assing, and A. sandiklicus Anlaş. Distributions of Eurysunius species in Western Turkey are mapped.